Tissue factor expression on the surface of monocytes from a patient with hereditary angioedema. Issue 10 (16th September 2014) - Iwamoto, Kazumasa; Morioke, Satoshi; Yanase, Yuhki; Uchida, Kazue; Hide, Michihiro
Abstract Hereditary angioedema (HAE) presents as severe angioedema, which is mostly due to the C1 inhibitor (C1‐INH) gene mutations. Environmental factors, minor trauma and oral contraceptives have been reported to induce angioedema attack, but the trigger may often be uncertain. Activated factor XII controlled by C1‐INH facilitates bradykinin generation and also regulates coagulation cascade, but the relationship between edema formation and coagulation is still unclear. We have described a 35‐year‐old female patient with HAE, presenting with frequent angioedema attacks in the absence of an apparent triggering factor. She showed higher levels of FDP and D‐dimer during angioedema than those in remission. In addition, tissue factor (TF), an initiator of the extrinsic coagulation cascade, was expressed on the surface of monocytes. It was significantly higher than that of monocytes from healthy controls and tends to further increase during attacks. The expression of TF on monocytes may play a role in the induction of angioedema attacks in HAE by activating the coagulation pathway in association with reduced functions of C1‐INH.